Strategi Internalisasi Nilai-nilai Moderasi Beragama dalam Pembelajaran Bahasa Indonesia di SMA - Heryati, Yeti; Kosim, Abdul; Gunawan, Heri; Rahman, Ahmad Syaeful; Bustomi; Hoerudi, Cecep Wahyu (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study examines the strategies for internalizing the values of religious moderation within Indonesian language instruction in schools. Religious moderation—emphasizing tolerance, balance, and respect for diversity—is highly relevant to students' character formation in Indonesia's pluralistic society. Data were collected through in-depth interviews and classroom observations at SMA Cordova Bandung using a qualitative approach. The findings reveal that Indonesian language teachers utilize interactive lectures, group discussions, contextual learning, and project-based learning methods to embed religious moderation values. some students experience difficulty in fully grasping the concept of religious moderation. The study concludes that integrating religious moderation into Indonesian language learning can effectively contribute to character building when approached through contextual and life-based pedagogy.